A Comparative Quasi-Experimental Study of Beetroot–Red Guava Juice and Salak Pondoh Juice on Hemoglobin Levels in Pregnant Women with Anemia in Depok, Indonesia - Cholisah Suralaga; Triana Indrayani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Anemia remains a common concern during pregnancy due to increased iron requirements. Alternative nutritional approaches from natural food sources may help improve hemoglobin levels, particularly among women who are reluctant to consume iron supplements. This study aimed to compare the effectiveness of beetroot–red guava juice and salak pondoh juice in increasing hemoglobin levels among third-trimester pregnant women with anemia. Methods: This research employed a quasi-experimental design with a pretest-posttest control group methodology. Purposive sampling was used to choose 150 anemic pregnant women in their third trimester. Participants were categorized into two groups: Seventy-five participants were administered beets combined with red guava juice (intervention group), whereas another seventy-five participants received salak pondoh juice (comparison group). Hemoglobin levels were evaluated pre- and post-intervention utilizing a hemoglobin assessment observation sheet. Data were analyzed utilizing paired t-tests to evaluate within-group differences and independent t-tests to compare inter-group differences. Results: The average elevation in hemoglobin levels was 0.46 g/dL (95% CI: 0.35–0.57) for the beetroot–red guava group and 0.34 g/dL (95% CI: 0.32–0.37) for the salak pondoh group. The intergroup difference was 0.30 g/dL (95% CI: 0.15–0.45), indicating a moderate effect size (Cohen’s d = 0.62). The effect size analysis indicated a substantial effect in the beetroot–red guava group (Cohen’s d = 0.92) and an exceedingly large effect in the salak pondoh group (Cohen’s d = 3.2). The intergroup comparison produced a moderate effect size (Cohen’s d = 0.62). Conclusion: These findings indicate short-term increases in hemoglobin levels associated with both interventions. However, the modest magnitude of change and short duration of intervention warrant cautious interpretation and further longitudinal investigation.